Decoding volatile-microbial-physicochemical interplay of sensory preference in commercial shrimp paste based on flavoromics and high-throughput sequencing - Mengyue Hu; Ling Zhao; Huihui Sun; Qi Liu; Yong Xue; Rong Cao (Current Research in Food Science)
Despite the long-standing tradition of shrimp paste in China, the aroma profiles driving consumer preferences remain poorly characterized. This study applied flavoromics and high-throughput sequencing to analyze nine commercial shrimp pastes, aiming to identify critical odorants influencing sensory acceptance and investigate their correlation with physicochemical properties and microbial communities. Nine distinct aroma attributes were identified as significant determinants of consumer preferences. Comprehensive volatile profiling using GC-IMS and GC-MS detected 44 and 40 volatiles, respectively, with 30 identified as aroma-active compounds (odor-active value ≥ 1). According to partial least squares regression analysis, fourteen key AACs significantly contributed to aroma attributes. Desirable AACs including 2,3-butanedione, isoamyl acetate, benzaldehyde, 2-heptanone, dimethyl trisulfide, 2,6-dimethyl pyrazine, 2,5-dimethyl pyrazine, and trimethyl pyrazine were associated with aroma attributes, such as sweet, meaty, cooked-garlic-like, sesame oil-like, and soy sauce-like aromas. Conversely, six AACs, including 3-methyl butanoic acid, naphthalene, trimethylamine, indole, 1-penten-3-ol, and Z-3-hexen-1-ol, contributed to off-odors characterized as pungent, earthy, rotten, and fishy. Significant variations were observed in physicochemical parameters and microbial composition, with dominant genera including Tetragenococcus, Corynebacterium_1, Vagococcus, Acinetobacter, Alkalibacterium, and Psychrobacter showing strong correlations with aroma formation. Metabolic pathway analysis revealed that microbial enzymatic activities-particularly decarboxylation, deamination, lysis, and lipid oxidation-critically shape the volatile profile through the degradation of amino acids and polyunsaturated fatty acids. This work systematically deciphers the molecular basis of shrimp paste flavor, providing actionable insights for optimizing fermentation processes to enhance sensory quality and consumer acceptance.